Strategi Pembelajaran Al-Qur’an Pada Tigkat Usia Dasar: Analisis Pada Materi Kandungan Al-Qur’an - Arifin, Zainul; Tambunan, Siti Khadizah (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2024)
This study aims to analyze the Qur'an learning strategies implemented at MIS Islamiyah, particularly in relation to the content of the Qur'an. Various strategies, such as lectures, discussions, the use of digital media, and contextual approaches, are employed to enhance students' understanding of the content of the Qur'an. The results of the study indicate that digital media, such as educational videos and interactive applications, are effective in increasing students' interest and facilitating more flexible learning. Students are also able to better understand the meaning and moral messages contained in the Qur'an through a contextual approach that relates the teachings of the Qur'an to real life. However, the main challenges faced are time constraints, uneven technological infrastructure, and difficulties in understanding the context of certain verses. This study makes an important contribution to developing Qur'an learning strategies in Madrasah Ibtidaiyah by offering insights into the challenges faced and providing recommendations for improving the effectiveness of Qur'an learning through innovative approaches and more in-depth digital media.